Perencanaan Jadwal Induk Produksi Dengan Menggunakan Metode Disagregat Guna Memenuhi Permintaan Yang Berfluktuasi - Eti Kristinawati (Department Industrial Engineering, University of Muhammadiyah Malang, 2000)
Every company always tries to serve all customer's demand. This need a good planning and schedulling to keep flow production. PT Binarenata is one company which produce many kind of metal products. Currently, this company has problem in material handling of product and lack of another product. To solve this problem, this company made Master Produclion Schedule using disagregat method to duet he fluctuation demand. From analysis data can be found the number of worker with minimum cost in the next production planning is about 966 persons with cost about Rp. 49.431.714.000,00. Implementing this Master Production Schedule can reduce production cost about Rp. 5.829.363.807,00 or 76,3 %